Subchronic Oral Toxicity of Sodium p-Hydroxybenzoate in Sprague-Dawley Rats - Fan, Xiaoli; Song, Hengzhi; Xu, Xiaotian; Lu, Xi; Wang, Yuhui; Duan, Xiaoqun (Frontiers in Pharmacology, 2022)
p-Hydroxybenzoic acid (p-HBA), which exists extensively in plants, is well known for its anti-inflammatory effects, but various adverse side effects have also been reported. Previous research has found that acid translated to its sodium salt improves the safety profile of compounds. Therefore, we hypothesized that p-HBA translated to sodium p-hydroxybenzoate would improve its safety profile. In the present study, we evaluated the toxicity of sodium p-hydroxybenzoate after 90 days of repeated oral toxicity experiments according to OECE guidelines in male and female Sprague–Dawley rats. Sodium p-hydroxybenzoate was administered orally to SD rats at doses of 0, 125, 250, and 500 mg/kg body weight (BW)/day for 90 days. All animals survived to the end of the study, and no sodium p-hydroxybenzoate treatment-associated mortality or clinical changes were observed during the study period. Sodium p-hydroxybenzoate did not promote any clinical signs of toxicologically relevant effects, including changes in body weight, food intake and urinalysis parameters, in male or female SD rats. Dose-related alterations in hematological parameters, organ weights and histopathological findings in hepatic tissue were examined in animals of both sexes in the 500 mg/kg BW/day group. Based on the study, the no-observed-adverse-effect level (NOAEL) for sodium p-hydroxybenzoate was determined to be 250 mg/kg BW/day in both male and female rats.